Responsible use of crop protection products and Nigeria's growth enhancement support scheme - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
We examine the impact of the federal government of Nigeria's (FGN) growth enhancement support scheme (GESS) on responsible use of crop protection products (CPPs) in rural Nigeria. Results from the use of logistic regressions show that GESS significantly impact on farmers' access to CP Ps, but does not significantly impact on farmers' knowledge and skill of CPP application, and in several cases the misuse has led to deterioration of soil fertility. Findings suggests that embracing information on recommended CPPs, dose rates, dilutions, timing, frequency of applications and precautions should form the foundation of GESS activity attributable to CPPs in sub-Saharan Africa.
Keywords: Q10; Q14; L96; O40; O55; 330; Growth enhancement support scheme; crop protection products; Mobile technology; Smallholder farmers; Rural Nigeria